2014
DOI: 10.1007/s12263-014-0395-5
|View full text |Cite
|
Sign up to set email alerts
|

An interaction effect between glucokinase gene variation and carbohydrate intakes modulates the plasma triglyceride response to a fish oil supplementation

Abstract: A large inter-individual variability in the plasma triglyceride (TG) response to fish oil consumption has been observed. The objective was to investigate the gene-diet interaction effects between single-nucleotide polymorphisms (SNPs) within glucokinase (GCK) gene and dietary carbohydrate intakes (CHO) on the plasma TG response to a fish oil supplementation. Two hundred and eight participants were recruited in the greater Quebec City area. The participants completed a 6-week fish oil supplementation (5 g fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…It is currently unclear what the actual association with type 2 diabetes is for the GCKR (rs780094) derived allele. In a study of the other SNP, GCKR (rs741038), for which the ancestral allele was associated with both hypertriglyceridemia and low HDL in our study, other researchers showed the greatest decrease in TG in over weight subjects (Canadians; n= 208; 96 male, 112 Female; age 30.82 ± 8.66; BMI 27.84 ± 3.73) with the derived allele of GCKR (rs741038) after fish oil supplementation when on a high carbohydrate diet [28] . These data suggest that those with the ancestral allele may not benefit from n-3 fish oil as much as those with the derived allele.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…It is currently unclear what the actual association with type 2 diabetes is for the GCKR (rs780094) derived allele. In a study of the other SNP, GCKR (rs741038), for which the ancestral allele was associated with both hypertriglyceridemia and low HDL in our study, other researchers showed the greatest decrease in TG in over weight subjects (Canadians; n= 208; 96 male, 112 Female; age 30.82 ± 8.66; BMI 27.84 ± 3.73) with the derived allele of GCKR (rs741038) after fish oil supplementation when on a high carbohydrate diet [28] . These data suggest that those with the ancestral allele may not benefit from n-3 fish oil as much as those with the derived allele.…”
Section: Discussionmentioning
confidence: 61%
“…A higher dietary intake of omega-3 polyunsaturated fatty acids (PUFA) was associated with a detrimental increase in plasma APOC3 in those individuals with the CC polymorphism APOC3 (rs2854116) [27] . However, fish oil supplementation was found to lower triglyceride (TG) levels in human subjects homozygous for GCKR (rs741038) [28] . Genetic polymorphisms exacerbated by dietary factors may play a role in the pathogenesis of NAFLD in all populations or perhaps only individuals at risk for obesity or type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, dopamine, which is synthesized from the AAs, phenyalanine and tyrosine, was also associated with obesity in the US women. An elevated BCAA and AA profile in obese individuals has previously been associated with a Westernized diet, typically characterized by high levels of protein and fat intake (Newgard et al 2009; Bouchard-Mercier et al 2014). Ghanaian women, consumed significantly less protein and fat than their US and SA counterparts, which could partly account for their lower AA levels.…”
Section: Discussionmentioning
confidence: 99%
“…They have also been shown to interact with fatty acid desaturase (FADS) variants to affect low-density lipoprotein (LDL) cholesterol concentrations and obesity phenotype (85,86). Additionally, carbohydrate intake has also been reported to interact with glucokinase genetic variation to affect plasma triglycerides (57). …”
Section: Introductionmentioning
confidence: 99%